DIGITAL NATIVE CHARACTER IN SOCIAL MEDIA INTERPRETATION: A STUDY ON INSTAGRAM ACCOUNTS, @QURANREVIEW - Izzuthoriqul Haq; Muhammad Labib Syauqi (UIN Raden Mas Said Surakarta, 2021)
This study aims to examine the methods, processes of interpretation (tafsir), and religious discourses that develop on social media, as well as the implications and effectiveness of its interpretation for the readers. It is a case study of the Instagram account @qur'anreview. Amid the trend of Qur€™an interpretation on social media, this @qur'anreview account has attracted the attention of netizens through its religious content presentation in the form of interpretation as its language style, diction, and nuances meet the millennial generation. Based on the hermeneutic, critical discourse analysis, and mass communication effect theoretical approach, the results of the study show that the religious content presented by the @quranreview account focuses on the language approach presented in the form of thematic interpretation. The interpretation follows the opportunistic and omnivorous characteristics of the digital native. The interpretation model is quite effective and has implications for the cognitive, affective, and behavioral aspects of the readers. While the social space of its interpretation is based on the culture of social media and digital native, which leads to popular Islamic discourse.